Diagnóstico actual y alternativas de tratamiento médico en diabetes mellitus tipo 2 - Araya Q., Verónica (Revista Hospital Clínico Universidad de Chile, 2012)
The goal of the therapy in type 2 diabetes is defined according to hemoglobin A1c (HbA1c) level, which reflects chronic hyper glycemia. In 2009, an acceptable metabolic control was defined as HbA1c <7%. But recently, the American Diabetes Association (ADA) and theEuropean Association for the Study of Diabetes (EASD) released a consensus position on personalized HbA1c goals, centered in the patient. Available therapies to treat and control type 2 diabetes are reviewed; traditional therapies as metformin, sulfonylureas, and insulin and new therapies as GLP-1 analogues and DPP-4 inhibitors.